2019
DOI: 10.3390/su11061585
|View full text |Cite
|
Sign up to set email alerts
|

Improving Sustainability in Architectural Research: Biopsychosocial Requirements in the Design of Urban Spaces

Abstract: There is an ever increasing interest in identifying the links between architecture and public health and in how urban design can positively influence the latter. The psychology of sustainability and sustainable development represents an innovative research area as a recent contribution to sustainability science and its trans-disciplinary configuration. The research topic deals with the importance and the centrality of the user-centered approach in the observation of the relationships among mankind, technologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…In the literature, we observe that urban social sustainability refers to social equity [28,34], well-being and quality of life [6,35,36]. Social equity denotes justice and hence the equal distribution of resources: From the urban point of view, it refers to societies where there is no social and environmental exclusion; from the geographical point of view, it is representative of equal access to services in geographical areas [28].…”
Section: Theoretical Background: Social Sustainability and Sustainable Architecturementioning
confidence: 99%
See 2 more Smart Citations
“…In the literature, we observe that urban social sustainability refers to social equity [28,34], well-being and quality of life [6,35,36]. Social equity denotes justice and hence the equal distribution of resources: From the urban point of view, it refers to societies where there is no social and environmental exclusion; from the geographical point of view, it is representative of equal access to services in geographical areas [28].…”
Section: Theoretical Background: Social Sustainability and Sustainable Architecturementioning
confidence: 99%
“…Social equity denotes justice and hence the equal distribution of resources: From the urban point of view, it refers to societies where there is no social and environmental exclusion; from the geographical point of view, it is representative of equal access to services in geographical areas [28]. Strong societies are characterised by social cohesion and inclusion, based on social interaction, where well-being and quality of life are considered key objectives of sustainable development [36]. Well-being is a broad concept that refers to the state of being happy and healthy from the physical, mental, spiritual and social points of view [6,36].…”
Section: Theoretical Background: Social Sustainability and Sustainable Architecturementioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Santi, Leporelli, and Di-Sivo consider the interrelation between urban architecture, sustainability, and health, concluding that the role of designers, in the field of architecture and urban planning, becomes significant in the realisation of democratic and sustainable urban contexts for the direct connections established with the policy of interventions, government actions, and social cohesion [52] (p. 1). In the next section, we analyze some example of interventions in this sense, but in which the media has played a key role.…”
Section: Resultsmentioning
confidence: 99%
“…An increasing number of studies have shown primary preventive approaches in the domain of sustainable sciences (e.g., Leporelli and Santi, 2019 ; Santi et al, 2019 ; Chotchoungchatchai et al, 2020 ; Nowacki et al, 2020 ), and scholars have advanced these interventions to foster the strengths of the employees (e.g., Di Fabio, 2019 ; Di Fabio and Duradoni, 2019 , 2020 ). However, future studies are needed to expand knowledge on positive strength-based primary preventive interventions in vulnerable workers.…”
Section: Enriching the Positive Perspective For Marginalized And Vulnerable Workers: Positive Healthy Organizations And Strength-based Prmentioning
confidence: 99%